Simultaneous quantification of cyclosporin, tacrolimus, sirolimus and everolimus in whole blood by UHPLC–MS/MS for therapeutic drug monitoring. (2nd February 2021) - Antunes, Natalicia J.; Kipper, Karin; Couchman, Lewis; Duncan, Marie‐Anne; Holt, David W.; De Nucci, Gilberto; Johnston, Atholl
Abstract: The aim of this study was to develop and validate a UHPLC–MS/MS assay to quantify cyclosporin (CYC), tacrolimus (TAC), sirolimus (SIR) and everolimus (EVE) in human whole blood for therapeutic drug monitoring. Analytes were extracted from 50 μL human whole blood by protein precipitation. The separation of the drugs was performed on an Acquity UPLC BEH C18 column. Analytes were eluted with a mobile phase consisting of 2 mM ammonium acetate with 0.1% formic acid (v/v) in deionised water and 2 mM ammonium acetate with 0.1% formic acid (v/v) in methanol at a flow rate of 300 μL/min in gradient elution. The method performance was evaluated by analysing patient blood samples and/or external quality control samples [proficiency testing (PT) scheme]. The method was linear from 23.75 to 1094.0, 1.3 to 42.4, 1.3 to 47.0 and 1.2–41.6 μg/mL for CYC, TAC, SIR and EVE, respectively. The within‐ and between‐assay reproducibility results were ˂ 11%. Results from PT and patient sample quantification were comparable to those obtained previously by an in‐house validated method using protein precipitation and liquid–liquid extraction. This method showed good analytical performance for quantifying CYC, TAC, SIR and EVE in whole blood over their respective calibration ranges.